2021
DOI: 10.3390/ijgi10030153
|View full text |Cite
|
Sign up to set email alerts
|

Development after Displacement: Evaluating the Utility of OpenStreetMap Data for Monitoring Sustainable Development Goal Progress in Refugee Settlements

Abstract: In 2015, 193 countries declared their commitment to “leave no one behind” in pursuit of 17 Sustainable Development Goals (SDGs). However, the world’s refugees have been routinely excluded from national censuses and representative surveys, and, as a result, have broadly been overlooked in SDG evaluations. In this study, we examine the potential of OpenStreetMap (OSM) data for monitoring SDG progress in refugee settlements. We collected all available OSM data in 28 refugee and 26 nearby non-refugee settlements i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…It has been shown that open data communities -such as OpenStreetMap (OSM) -are not only promising, but already contribute to filling existing data gaps 8,10,11 . OSM is now used widely for applications such as web maps and navigation services at and data about buildings from OSM has been used in domains such as urban planning 12 , SDG monitoring 13 , disaster management 11,14 , public health [15][16][17] , as well as during the COVID-19 pandemic 18 . However, particular attention needs to be paid to data quality, when OSM data is utilized in global studies or to derive global data products, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that open data communities -such as OpenStreetMap (OSM) -are not only promising, but already contribute to filling existing data gaps 8,10,11 . OSM is now used widely for applications such as web maps and navigation services at and data about buildings from OSM has been used in domains such as urban planning 12 , SDG monitoring 13 , disaster management 11,14 , public health [15][16][17] , as well as during the COVID-19 pandemic 18 . However, particular attention needs to be paid to data quality, when OSM data is utilized in global studies or to derive global data products, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The average stay in a UNHCR-managed refugee settlement was 10 years as of 2015 [28], though many settlements become intergenerational homes through a "protracted refugee scenario", in which refugee populations greater than twenty-five thousand people are displaced for more than five years [29]. The location, setting and timing of refugee settlements are broadly documented with openly accessible geospatial data on building footprints, settlement boundaries, as well as ancillary information on settlement population, refugee arrival and duration of habitation, much of which has been collected in support of rapid or prolonged humanitarian support [30].…”
Section: Introductionmentioning
confidence: 99%
“…According to an in-depth analysis by the authors of [33], the global datasets on built-up areas are less representative for IDP/refugee settlements, which are characterized by a low probability of detection, the underestimation of the built-up extent, and the complete overlooking of a few refugee settlements. A comprehensive assessment on the relevance of Open Street Maps (OSM) for monitoring the sustainable development goals in refugee settlements, by the authors of [34], also concludes that although OSM has relevant thematic layers for the intended goal, the information is mapped long after refugee settlements form, and it is not frequently updated. From the qualitative inspection made on the test site during the writing phase of this report, the underrepresentation of dwelling structures in IDP/refugee camps is also common in well-known generic open datasets, such as OpenStreetMap (OSM), Bing Maps, and Google Maps (Appendix A Figures A1 and A2 for details in specific study sites), and specific thematic layers hosted by entities working on IDP/refugee settlements [35].…”
Section: Introductionmentioning
confidence: 99%